Effects of intrathecal administration of orexin-1 receptor antagonist on antinociceptive responses induced by chemical stimulation of lateral hypothalamus in an animal model of tonic nociception. (June 2018) - Rezaee, Laleh; Karimi-Haghighi, Saeideh; Fazli-Tabaei, Soheila; Haghparast, Abbas
Abstract: Orexins are produced in the restricted regions of the lateral hypothalamus (LH). However, orexinergic receptors and projections are localized in wide regions like nucleus accumbens, ventral tegmental area, periaqueductal gray area and spinal cord which are involved in the pain modulation. This study was carried out to investigate the effects of intrathecal administration of orexin-1 receptor antagonist (SB-334867) in the spinal antinociception induced by intra-LH administration of carbachol (cholinergic receptor agonist) in both early and late phases of pain related behaviors in formalin test. In this study, pain-related behaviors (pain scores) were evaluated using the formalin test during 5-min block intervals for a 60-min period in seventy male Wistar rats were given SB-334867 (3, 10, 30 and 100 μM/10 μl) or vehicle (DMSO 12%; 10 μl) intrathecally following intra-LH administration of carbachol (250 nM/rat). Our data showed that intra-LH injection of carbachol attenuated the formalin-induced biphasic pain responses, and intrathecal administration of SB-334867 dose-dependently decreased LH stimulation-induced antinociceptive responses during both phases. Moreover, administration of different doses of SB-334867 during the early phase were more effective than those during the late phase. The antinociceptive role of orexinergic system in the formalin test through a neural pathway from the LH to the spinal cord provides evidence that orexins can be useful in therapeutic targets for pain relief. Highlights: Intra-LH carbachol reduced pain-related behaviors during the early and late phases of formalin test. Blockade of orexin-1 receptor in spinal cord attenuated the LH stimulation-induced antinociception. Reduction of nociceptive responses in early phase was more effective than those in late phase.